LEPRA LEPROMATOSA - Nájera Gómez, Juan (2017)
Leprosy is a chronic bacterial infection caused by Mycobacterium leprae, acid-fast bacilli forced to live in the intracellular space preferably in Schwann cells and macrophages, which affects the skin, nerves and eyes mostly. The existence of the disease has been known since ancient times, but still remains a serious public health problem worldwide, especially in endemic areas in Peru. Its clinical spectrum is given by the response generated by the immune system against the bacillus. Currently known various forms of disease presentation, including polar tuberculoid and lepromatous called, the indeterminate and borderline leprosy. Early diagnosis is the main tool to achieve proper treatment, prevent disabilities and rehabilitate the sick patient. The treatment set by the WHO in 1984 is a multidrug therapy based classification or multibacillary PB according to the number of lesions and the amount of bacilli present in the biopsy. We report the case of a male patient 50 years old, diagnosed with lepromatous leprosy. We discuss the diagnostic and treatment employed.